Mechanical and fracture properties of halloysite nanotube reinforced vinyl-ester nanocomposites - Alhuthali, Abdullah; Low, It-Meng (John Wiley and Sons Inc, 2013)
The mechanical and fracture properties of vinyl-ester composites reinforced with halloysite nanotubes have been investigated. Enhancements in toughness are attributed to crack bridging, deflection, and localized plastic deformation, while strength improvements can be attributed to the large aspect ratio of fillers, favorable interfacial adhesion and dispersion, and inter-tubular interaction. Comparisons of experimental data on elastic modulus and mathematical models for predicting particulate polymer composites have verified the models of Paul and Guth. The aspect ratio of fillers and the degree of interfacial adhesion are crucial factors in the prediction of elastic modulus in these polymer nanocomposites.